Primary biliary cholangitis: a comprehensive overview (2017)
Primary biliary cholangitis (PBC) is an autoimmune liver disease characterized by biliary destruction, progressive cholestasis, and potentially liver cirrhosis. Patients develop a well-orchestrated immune reaction, both innate and adaptive, against mitochondrial antigens that specifically targets intrahepatic biliary cells. A puzzling feature of PBC is that the immune attack is predominantly organ specific, although the mitochondrial autoantigens are found in all nucleated cells. The disease results from a combination of genetic and environmental risk factors; however, the exact pathogenesis remains unclear. Serologically, PBC is characterized by presence of antimitochondrial antibodies, which are present in 90–95 % of patients and are often detectable years before clinical signs appear. Like other complex disorders, PBC is heterogeneous in its presentation, symptomatology, disease progression, and response to therapy. A significant number of patients develop end-stage liver disease and eventually require liver transplantation. Recent studies from large international cohorts have better identified prognostic factors, suggesting a change in patient management based on risk stratification. Therapeutic options are changing. In this review we discuss data on the autoimmune responses and treatment of the disease. © 2017, Asian Pacific Association for the Study of the Liver.